A VLF EFFECTIVE GROUND CONDUCTIVITY MAP OF CANADA AND GREENLAND WITH REVISIONS DERIVED FROM PROPAGATION DATA. - Hauser,J. P.; Garner,W. E.; Rhoads,F. J. (1969)
Several airborne and ground-based experiments were conducted between 1959 and 1961 to investigate the propagation of very-low-frequency (vlf) radio waves over a large portion of Canada and Greenland. The results of these investigations have been reanalyzed in light of theoretical waveguide results to yield revisions to a vlf effective ground conductivity map of those areas developed through a correlation of geological and climatological data with conductivity. The experimental data confirm the theoretical attenuation rates for a daytime ionosphere with a height of 70 km and a gradient of 0.3/km for several effective ground conductivities from very high, such as seawater, down to as low as 0.00001 mho/m. There were also many indications that the theoretically determined excitation factors were substantiated by the experimental data for several values of receiving terminal foreground conductivity. A comparison of experimental propagation data with calculated values based on the theoretical model was used to modify the conductivity map. The confidence level of the original map was low in all areas where the conductivity was revised. Other propagation data, obtained over relatively long periods of time, were then used to demonstrate the accuracy of field-strength calculations based on the theoretical model and the modified conductivity map. These data also show that the daytime ionospheric gradient for the northern latitude paths investigated changes from 0.3/km around equinox to about 0.5/km in midsummer. (Author)